Managing in organisations: A practical guide - Elswarth, Tom (London Routledge, 2025)
Managing in Organisations is a concise, accessible and practical approach to the difficult job of line management. It offers a kit of management tools and a range of worked examples that can be used to address the key tasks that managers face in the workplace. The book provides clear insights into how people behave everyday in real organisations. The fundamentals of key theories and sources is covered throughout for those coming to the subject for the first time.